Nanoparticle-Mediated Drug Delivery to Cervical Cells: Harnessing the Potential of Liposomes for Enhanced Therapeutic Efficacy - Mishra, Dr. Manoj; Chahal, Dr. Preeti (Migration Letters, 2023)
Cervical cancer continues to pose a substantial worldwide health obstacle, requiring novel treatment approaches. This research investigates the capacity of Nanoparticle-Mediated Drug Delivery to augment the efficacy of cervical cancer therapy. Highlighting the significance of precise medication delivery, using nanoparticles, namely liposomes, appears viable. Introducing a new method called Nanoparticle-Based Drug Delivery to Cervical Cells (NP-DD-CC) utilizes liposomes to accurately deliver medicinal substances while minimizing adverse effects on the whole body. The NP-DD-CC has remarkable characteristics, such as attaching nanocarriers to ligands to achieve target selectivity. The simulation findings provide diverse metrics for distinct Nanoparticle Densities: Localized Drug Concentration (67.76%), Reduction in Side Effects (48.5%), Overall Patient Tolerance Increase (40.4%), and Nanoparticle Retention Improvement (73%). NP-DD-CC presents a promising advancement in the treatment of cervical cancer by enhancing the accuracy of medication administration and reducing the occurrence of adverse side effects.